Implementasi Model IBMR Berbantu PhET Simulation untuk Meningkatkan Kemampuan Representasi pada Pembelajaran Fisika - Joko Siswanto (Jurnal Penelitian Pembelajaran Fisika, 2019)
This study aims to analyze the effectiveness of the IBMR learning model assisted by phet to improve the ability of representation in physics learning. The research design used quasi-experiment one group pre-test and post-test conducted on 20 students of Information Technology Education at Universitas PGRI Semarang who programmed basic physics courses. The research data was collected from pre-test and post-test the ability of representation supported by observations of the implementation of learning. Data analysis uses paired t-test and n-gain to calculate and determine the criteria of increase of the representation ability. The results showed that the implementation of the IBMR model assisted by phet simulation was effective in increasing the ability of representation of students with gain score <g> = 0,59 (moderate criteria).